2014
DOI: 10.22226/2410-3535-2014-4-218-221
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of the atomic clusters over the (111) and(100) surfaces in Ni crystal

Abstract: Diffusion of the atomic clusters over Ni (111) and (100) surfaces is studied by the molecular dynamics simulation. The activation energies of diffusion of the clusters of different sizes are calculated. It is shown, that cluster's atoms migrate over the surface by individual movement instead of collective motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An increase in activation energy with increasing cluster size is typical, not only Previously [8], it was shown that, at a constant temperature, the activation energy is higher when larger clusters participate in the viscous flow of a liquid. An increase in activation energy with increasing cluster size is typical, not only for viscous fluid flow, but for other transport phenomena [28][29][30]. Thus, when heated in a low-temperature region with the lowest activation energy, small clusters contribute to the viscous flow of the melt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in activation energy with increasing cluster size is typical, not only Previously [8], it was shown that, at a constant temperature, the activation energy is higher when larger clusters participate in the viscous flow of a liquid. An increase in activation energy with increasing cluster size is typical, not only for viscous fluid flow, but for other transport phenomena [28][29][30]. Thus, when heated in a low-temperature region with the lowest activation energy, small clusters contribute to the viscous flow of the melt.…”
Section: Resultsmentioning
confidence: 99%
“…The electronegativity of aluminum on the Luo-Benson scale is 2.40 and is midway between iron and boron. Therefore, aluminum atoms attract both iron atoms and boron atoms with the formation of clusters, based on the stable ternary phase Fe 2 AlB 2 [29,30] with high formation energy (see Table 2) or higher-order metastable phases Fe 3 AlB 4 and Fe 4 AlB 6 [33].…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that (111) orientation would be a preferred growth direction if no additional energy is provided to the deposited atoms. In addition, Poletaev et al have also indicated that the activation energy for the migration for Ni atoms in (100) plane is multiple times higher than in (111) plane [31]. Both silver and nickel are transition metals and have FCC crystal structure.…”
Section: Characterizationsmentioning
confidence: 99%